O efeito da intervenção psicológica em pacientes internados com doença pulmonar obstrutiva crônica (DPOC) - Keske, Sérgio (Universidade do Vale do Rio do Sinos, 2008)
The Chronic Obstructive Pulmonary Disease (COPD) is a pathology often accompanied by an increase of anxiety and depression symptoms. The goal of this dissertation was the inquiry on the effects of a cognitive-behavioral psychological intervention associated to a psychoeducation of anxiety and depression symptoms, as well as quality of life, in patients with COPD. 22 patients randomly divided into three groups participated in the research. The patients of the first group (n=7) received the hospital’s medical standard of care. The second group (n=8) received the medical standard of care and cognitive-behavioral therapy sections (CBT) and the third group (n=7) received the procedures mentioned before with one psychoeducation section added. The participants were evaluated before and after the treatment, with the Beck Anxiety and Depression Inventory and the Saint George’s Respiratory Questionnaire (SGRQ), to quality of life. The data were analyzed with techniques from non-parametric statistics to repeated measur
Keywords: ansiedade; depressão; psicoeducação; terapia cognitivo-comportamental; DPOC; cognitive-behavioral therapy; depression; psychoeducation; anxiety; COPD; Ciências Humanas